2001
DOI: 10.1002/ana.1255
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of secondary‐progressive multiple sclerosis

Abstract: Twenty-three plaques obtained at early autopsy from 2 patients with secondary-progressive multiple sclerosis were examined immunohistochemically for microglia/macrophages, and for immunoglobulins and components of activated complement. Most of the lesions examined in both cases exhibited evidence of low-grade active demyelination of an unusual type (frustrated phagocytosis) in periplaque white matter. This included linear groups of microglia engaging short segments of disrupted myelin that were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
312
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(333 citation statements)
references
References 68 publications
16
312
2
3
Order By: Relevance
“…Double-immunostaining for microglial markers and C3b/iC3b showed colocalization, similar to our findings in Crry −/− mice, suggesting an interaction between axonal C3b/iC3b and its receptor on microglia. Activated C3 was independently identified in association with ramified microglia in perilesional white matter bordering plaques (19,20), IL-1β was up-regulated in the rim but not the perilesional white matter, whereas C3 was up-regulated in the rim and the perilesional white matter of chronic active lesions (18). Complement activation in MS suggests local dysregulation; in support of this, we have recently shown that plasma fH levels predict the clinical course of MS (34).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Double-immunostaining for microglial markers and C3b/iC3b showed colocalization, similar to our findings in Crry −/− mice, suggesting an interaction between axonal C3b/iC3b and its receptor on microglia. Activated C3 was independently identified in association with ramified microglia in perilesional white matter bordering plaques (19,20), IL-1β was up-regulated in the rim but not the perilesional white matter, whereas C3 was up-regulated in the rim and the perilesional white matter of chronic active lesions (18). Complement activation in MS suggests local dysregulation; in support of this, we have recently shown that plasma fH levels predict the clinical course of MS (34).…”
Section: Discussionmentioning
confidence: 71%
“…(17) and may range from quiescent to highly activated morphology. Microglial expression of IL-1β (18) and deposition of activated C3 (C3d) (19,20) have been independently reported but no account has been published of an investigation in the same lesion/patient or analysis in the context of microglial priming. MS brain tissue and white matter from nondemented controls (Table S1) were examined for evidence of microglial priming by morphology, staining for all three subunits (HLA-DP, HLA-DQ, and HLA-DR) of the HLA (HLA-DP-DQ-DR), IL-1β, and C3 fragment (C3b/iC3b) deposition (Table S2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Many reported histological patterns are reflective of different evolution stages: from acute active plaques with abundant macrophages and myelin breakdown, to active (smoldering) rim lesions with macrophage presence concentrated at the rim, to inactive plaques without myelin breakdown. 4 Recent studies also showed remyelination to be more extensive than previously assumed, 47 giving new impetus to the search for an in vivo marker of repair and calling for new paraclinical markers of how tissue destruction occurs in vivo. 48 The residual heterogeneity of lesion patterns observed in time-series analysis studies implies similar variability in progression and destructive nature of lesion formation.…”
Section: Discussion: Pathophysiological and Etiological Interpretationsmentioning
confidence: 99%
“…4 An altered role of inflammation in SPMS is documented also from multiple treatment trials in which inflammation was effectively suppressed but accrual of atrophy remained unaltered. [5][6][7] …”
Section: The Repair Potential Hypothesismentioning
confidence: 98%
See 1 more Smart Citation